2014
DOI: 10.1007/s40615-014-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

The Home Physical Activity Environment and Adolescent BMI, Physical Activity, and TV Viewing: Disparities Across a Diverse Sample

Abstract: Objective Characteristics of the home and family have been associated with adolescents' BMI and physical and sedentary activity, but few studies have examined how these characteristics vary across ethnic/racial groups. This study explores whether recommendations for activity promotion are equally relevant to different adolescent populations. Design Participants included 2,374 adolescents and their parent(s), recruited through 20 public schools in Minneapolis/St. Paul, MN in 2009-2010. Ethnic/racial groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Our study found that adolescents in Texas who had parents that disapproved of them not exercising and who received parental support for physical activity had lower odds of engaging in two or more hours of screen-time per day and higher odds of engaging in both five or more days of moderate physical activity per week and three or more days of vigorous physical activity per week. These results are consistent with previous studies that showed that parental support influenced child and adolescent physical activity and sedentary time [69, 28, 29].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that adolescents in Texas who had parents that disapproved of them not exercising and who received parental support for physical activity had lower odds of engaging in two or more hours of screen-time per day and higher odds of engaging in both five or more days of moderate physical activity per week and three or more days of vigorous physical activity per week. These results are consistent with previous studies that showed that parental support influenced child and adolescent physical activity and sedentary time [69, 28, 29].…”
Section: Discussionsupporting
confidence: 93%
“…Another study from Israel reported that PA participation was different between adolescents from different ethnic backgrounds (Jews and Arabs), which could lead to health disparities [ 44 ]. This is in line with the other studies that have found that the differences in PA levels were associated with the ethnic backgrounds in adolescents [ 64 , 65 ]. Therefore, it is suggested that “race/ethnicity” and/or cultural backgrounds should be a consideration in the design of future studies investigating factors that influence PA participation.…”
Section: Discussionsupporting
confidence: 93%
“…However, more than half of the children fail to meet this recommendation and spend excessive time in sedentary behavior. Additionally, racial and ethnic differences are even more evident [10]. Schools are imperative settings for ethnic minority children from lower socioeconomic households to be physically active, because they often have less physical activity-related equipment outside of school (at home and in the community) and spend a substantial amount of time on media devices for entertainment [10].…”
Section: Introductionmentioning
confidence: 99%